Can the Wet – State Conductivity of Hydrogels be Improved by Incorporation of Spherical Conducting Nanoparticles?. (2nd January 2015) - Schirmer, Katharina; Wright, Cody; Warren, Holly; Thompson, Brianna; Quigley, Anita; Kapsa, Robert; Wallace, Gordon
ABSTRACT: In nerve and muscle regeneration applications, the incorporation of conducting elements into biocompatible materials has gained interest over the last few years, as it has been shown that electrical stimulation of some regenerating cells has a positive effect on their development. A variety of different materials, ranging from graphene to conducting polymers, have been incorporated into hydrogels and increased conductivities have been reported. However, the majority of conductivity measurements are performed in a dry state, even though material blends are designed for applications in a wet state, in vivo environment. The focus of this work is to use polypyrrole nanoparticles to increase the wet–state conductivity of alginate to produce a conducting, easily processable, cell–supporting composite material. Characterization and purification of the conducting polymer nanoparticle dispersions, as well as electrochemical measurements, have been performed to assess conductivity of the nanoparticles and hydrogel composites in the wet state, in order to determine whether filling an ionically conducting hydrogel with electrically conductive nanoparticles will enhance the conductivity. It was determined that the introduction of spherical nanoparticles into alginate gel does not increase, but rather slightly reduces conductivity of the hydrogel in the wet state.